Microstructure and Mechanical Properties of Ultrafine-Grained Interstitial-Free Steel Processed by ECAP - Verma D.; Mukhopadhyay N.K.; Sastry G.V.S.; Manna R. (My University, 2025)
Equal-channel angular pressing (ECAP) of interstitial-free (IF) steel at equivalent strain, εvm = 12 has been employed to develop ultrafine-grained (UFG) microstructure with high fraction of low angle grain boundaries, that enhances strength significantly with reduced tensile ductility. ECAPed IF steel has been deformed further by cold rolling/cryorolling at −50 °C to >90 % reduction in area. It is observed that the UFG structure gets refined with an improvement in high angle grain boundary fraction and heavily stressed non-equilibrium grain boundaries in cryorolled state resulting in significant strengthening. However, the decrease in grain size to an ultrafine level with the increased lattice strain lowers the work hardening ability of the material that limits its ductility. Hence, the rolled samples are flash annealed at 675 °C in order to recover the ductility of the material by achieving partially recrystallized structures. Consequently, the increased subgrain size as well as the grain size, the reduced residual lattice strain, lower hardness and strength with marginal recovery of ductility is maintained in order to attain the yield strength 2–3 times compared to that of as-received coarse-grained IF steel. © 2016, The Indian Institute of Metals - IIM.